2014
DOI: 10.1007/s13224-013-0491-2
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Cesarean Delivery: Rate and Indications

Abstract: Objectives To compare the cesarean delivery rates over the last decade and to examine the indications contributing to changed trends, if any. Methods To compare the rate and indications of cesarean delivery over the last decade, the data were collected in a retrospective manner from all the deliveries that occurred between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 13 publications
(19 reference statements)
4
25
1
Order By: Relevance
“…Fetal distress was found to be the largest contributor to primary cesarean delivery as per other studies. 5,6 Previous LSCS was the third most common indication in both the groups in this study. In a study conducted in Gujarat, previous LSCS turned out to be the most common indication, fetal distress, breech and prolonged labour following it.…”
Section: Discussionmentioning
confidence: 63%
“…Fetal distress was found to be the largest contributor to primary cesarean delivery as per other studies. 5,6 Previous LSCS was the third most common indication in both the groups in this study. In a study conducted in Gujarat, previous LSCS turned out to be the most common indication, fetal distress, breech and prolonged labour following it.…”
Section: Discussionmentioning
confidence: 63%
“…3 Similarly, from India, Mittal et al reported an increase in primary CS rate from 69.03 % to 72.62 % over a ten-year period. 4 These studies suggest that analysis of CS rates should focus on the primary CS rates. This comparative study analysed primary CS rates and related factors based on parity.…”
Section: Discussionmentioning
confidence: 99%
“…Caesarean section is one of the commonly performed surgical procedures in obstetrics. 1 It was introduced in clinical practice as a lifesaving procedure for the mother and/or the baby.One of the most dramatic features of modern obstetrics is the increase in caesarean section rates. 2,3 Caesarean section rate has increased in different parts of the world, both in developed and developing countries over the last three decades.…”
Section: Introductionmentioning
confidence: 99%